Identification of an Asexual Reproduction Inducer of Phytopathogenic and Toxigenic Fusarium. Issue 27 (30th May 2018) - Qi, Jianhua; Cheng, Lihong; Sun, Yujuan; Hirata, Yushi; Ushida, Naoki; Ma, Zhonghua; Osada, Hiroyuki; Nishikawa, Toshio; Xiang, Lan
Abstract: Asexual and sexual reproduction are the most important biological events in the life cycle of phytopathogenic and toxigenic Fusarium and are responsible for disease epidemics. However, the signaling molecules which induce the asexual reproduction of Fusarium are unknown. Herein we describe the structure elucidation, including the absolute configuration, of Fusarium asexual reproduction inducer (FARI), a new sesquiterpene derivative, by spectroscopic analysis, total synthesis, and conidium‐inducing assays of synthetic isomers. We have also uncovered the universality of FARI among Fusarium species. Moreover, a mechanism‐of‐action study suggested that the Gpmk1 and LaeA signaling pathways are required for conidium formation induced by FARI; conversely, the Mgv1 of mitogen‐activated protein kinase is not involved in conidium formation. FARI exhibited conidium‐inducing activity at an extremely low dose and high stereoselectivity, which may suggest the presence of a stereospecific target. Abstract : A way to fight blight in sight : Fusarium asexual reproduction inducer (FARI), a newly discovered sesquiterpene derivative, induced the formation of conidia (see micrographs) in notorious Fusarium graminearum at an extremely low dose. The universality of FARI among Fusarium species was uncovered. Furthermore, a mechanism‐of‐action study revealed that Gpmk1 and LaeA signaling pathways are required for conidium formation induced by FARI.